2015
DOI: 10.1128/genomea.01346-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Thermus scotoductus Strain K1, Isolated from a Geothermal Spring in Karvachar, Nagorno Karabakh

Abstract: The 2,379,636-bp draft genome sequence of Thermus scotoductus strain K1, isolated from geothermal spring outlet located in the Karvachar region in Nagorno Karabakh is presented. Strain K1 shares about 80% genome sequence similarity with T. scotoductus strain SA-01, recovered from a deep gold mine in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…scotoductus SA‐01. This finding was expected, as according to earlier evaluations of the 16S rRNA gene sequences from these bacteria, they showed >99% similarity (Saghatelyan et al, 2015). Ts K1 DNA polymerase is relatively different from T .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…scotoductus SA‐01. This finding was expected, as according to earlier evaluations of the 16S rRNA gene sequences from these bacteria, they showed >99% similarity (Saghatelyan et al, 2015). Ts K1 DNA polymerase is relatively different from T .…”
Section: Discussionsupporting
confidence: 75%
“…The amino acid sequence comparison showed that this enzyme shares a high degree of similarity to DNA polymerase from T. scotoductus SA-01. This finding was expected, as according to earlier evaluations of the 16S rRNA gene sequences from these bacteria, they showed >99% similarity (Saghatelyan et al, 2015). TsK1 DNA polymerase is relatively different from T. aquaticus DNA polymerase, which might explain the differences in the behavior of this enzyme as discussed below.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In total, more than 130 strains of 40 distinct species belonging to 22 different genera, namely Bacillus, Geobacillus, Parageobacillus, Anoxybacillus, Paenibacillus, Brevibacillus Aeribacillus, Ureibacillus, Thermoactinomyces, Sporosarcina, Thermus, Rhodobacter, Thiospirillum, Thiocapsa, Rhodopseudomonas, Methylocaldum, Desulfomicrobium, Desulfovibrio, Treponema, Arcobacter, Nitrospira , and Methanoculleus , have been isolated from the hot springs in Armenia and Nagorno-Karabakh. Among these isolates, many prospective strains have been selected for future studies to explore their potential in white (industrial), green (agricultural), and red (pharmaceutical) biotechnology [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Microbiological Analysismentioning
confidence: 99%